Impact of Early Salvage Androgen Deprivation Therapy in Localized Prostate Cancer after Radical Prostatectomy: A Propensity Score Matched Analysis - Park, Jae Won; Jang, Won Sik; Koh, Dong Hoon; Ham, Won Sik; Rha, Koon Ho; Hong, Sung Joon; Choi, Young Deuk (Yonsei medical journal, 2018)
Androgen deprivation therapy (ADT) is used as a salvage treatment for men with biochemical recurrence (BCR) of prostate cancer (PCa) following initial radical prostatectomy (RP). The optimal time at which to begin salvage ADT (sADT) remains controversial. In this retrospective study, we evaluated the efficacy of initiating sADT in patients before prostate-specific antigen (PSA) values met the clinical definition of BCR. We identified 484 PCa patients who received sADT for BCR after RP. Median follow-up was 82 months. Propensity score matching was performed based on preoperative PSA level, pathologic T stage, and Gleason score. Patients were assigned to two groups of 169 patients each, based on PSA levels at the time of sADT: Group A (without meeting of the definition of BCR) and Group B (after BCR). Kaplan-Meier survival analyses and Cox regression analyses were performed. The median PSA level at sADT initiation was 0.12 ng/mL in group A and 0.42 ng/mL in group B. Kaplan-Meier analyses showed that group A had favorable disease progression-free survival (DPFS) and distant metastasis-free survival (DMFS), but did not have better cancer-specific survival (CSS) than group B. In subgroup analyses, group A showed better CSS rates in the non-organ confined PCa group. In Cox regression analyses, early sADT was associated significantly with DPFS and DMFS rates, however, did not correlate with CSS (p=0.107). Early sADT after RP improved DPFS and DMFS. Furthermore, early sADT patients demonstrated better CSS in non-organ confined PCa.